An Analisys Semantic of Utterance in Animated Film “Raya and The Last Dragon”: Penelitian - Laura S. Maitimu; Arini E Susanti (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Analysis semantic of utterance in Animated film “ Raya And The Last Dragon” is a study that explains the utterance used by the main characters in the in the film Raya and the Last Dragon. This study uses a qualitative descriptive method, the researcher will conduct direct observation of the utterance in the film. The film was produced by walt Disney, and directed by Carlos Lopez Estrada and Don Hall. The film Raya and the last Dragon depicts social conflict caused by prejudice, hatred, greed and a desire for power. The data collection technique used in this study is documentary analysis where the researcher captures several scenes that show the use of utterance and prosody. The results found in this film for utterance based on Heidi Lyn’s theory, there are 117 utterances using 9 types of utterances, including the Recipient type, Affirmative, Negative, Instrument, comitative, Agent, Action, Object, and Demonstrative. Where the type appears most often is the Recipient type.